2015
DOI: 10.1021/acs.analchem.5b03292
|View full text |Cite
|
Sign up to set email alerts
|

CIUSuite: A Quantitative Analysis Package for Collision Induced Unfolding Measurements of Gas-Phase Protein Ions

Abstract: Ion mobility-mass spectrometry (IM-MS) is a technology of growing importance for structural biology, providing complementary 3D structure information for biomolecules within samples that are difficult to analyze using conventional analytical tools through the near-simultaneous acquisition of ion collision cross sections (CCSs) and masses. Despite recent advances in IM-MS instrumentation, the resolution of closely related protein conformations remains challenging. Collision induced unfolding (CIU) has been demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
157
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(157 citation statements)
references
References 32 publications
0
157
0
Order By: Relevance
“…The impact of GAG binding upon the stability of the three-dimensional structure of FGF1 was examined using collision induced unfolding (CIU) experiments, an approach developed by Ruotolo and co-workers [47]. We performed a series of collision-induced activation experiments with incremental changes in trapping collisional energy (CE) applied to selected protein and protein complex ions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of GAG binding upon the stability of the three-dimensional structure of FGF1 was examined using collision induced unfolding (CIU) experiments, an approach developed by Ruotolo and co-workers [47]. We performed a series of collision-induced activation experiments with incremental changes in trapping collisional energy (CE) applied to selected protein and protein complex ions.…”
Section: Resultsmentioning
confidence: 99%
“…The CIU data was analyzed using CIUSuite [47]. CIU fingerprints of protein ions, which records the relative ion intensity (normalized and smoothed using Savitsky-Golay filter) as a function of collision energy and drift times, were shown in a 2-D contour plot using the CIUSuite plot function.…”
Section: Methodsmentioning
confidence: 99%
“…34 CID analysis of both chemical probes and reconstituted HSA complexes were carried out using Masslynx (Waters Corp. Manchester, UK)…”
Section: Methodsmentioning
confidence: 99%
“…For example, it can be used to infer the domain structure of proteins [154], or for studying the effect of ligand binding on protein stability [136]. Software packages have been developed for the quantitative comparison of CIU trajectories for this purpose [136,155], and to assist in data collection and analysis [156]. Recently, Laganowsky et al used a CIU approach to quantify the stabilization imparted on MPs by bound lipids, and found that lipids important for function enhance the resistance of MPs to CIU (e.g.…”
Section: Collision Induced Dissociation and Collision Induced Unfoldingmentioning
confidence: 99%